Predictive and Prognostic Value of Peritoneal Washing in Colorectal Cancer: A Literature Review - Sergey Iliev; Anislav Gabarski; Paulina Vladova; Pencho Tonchev; Ivailo Presolski; Kiril Nedyalkov (Journal of Biomedical & Clinical Research, 2018)
Over the last decade, there has been a steady trend in increasing the incidence of colorectal cancer on a global scale. The relative share of patients under the age of 40 increases with each year. There is also a tendency for the incidence to be almost the same in males and females. Despite the efforts of the National Cancer Institute (NCI) to establish and implement adequate screening for disease prevention, 45.8% of patients were diagnosed in the advanced (third and fourth) stages of the disease. In 44.7% of patients, it was in the first and second stages, and the stage was unspecified in the remainder [1].The prognosis in patients with colorectal cancer has been significantly improved. Precise staging of the tumor, adequate interpretation of predictive and prognostic factors is essential in the choice of therapeutic behavior. On the other hand, an inappropriate therapy administered to a patient with a diagnosed cancer can lead to disease progression, metastasis, and death, which can be avoided by adequate, patient-specified treatment.